1983
DOI: 10.1111/j.1365-2133.1983.tb07077.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous factors related to the risk of malignant melanoma

Abstract: In a case-control study, 287 women with malignant melanoma were compared with 574 age-matched controls. Red hair colour at age 5 years was associated with a tripling of risk [relative risk (RR) = 3.0], blonde hair with a 60% increase (RR = 1.6) and fair skin with a doubling (RR = 2.1). Women with melanoma also reported that they tended to burn (RR = 1.4) and to freckle (RR = 1.9) after exposure to sunlight. Since fair skin, red hair, and the tendency to burn or freckle after exposure to sunlight all cluster in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
1
3

Year Published

1984
1984
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(92 citation statements)
references
References 12 publications
3
85
1
3
Order By: Relevance
“…All studies which have examined for an association with long term pill use or for a possible (Beral et al, 1983). Both these factors are widely accepted as being important determinants of melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies which have examined for an association with long term pill use or for a possible (Beral et al, 1983). Both these factors are widely accepted as being important determinants of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly similar relationships were found for "new" cases and "old" cases, as is shown in Table II, and so most analyses pool the two groups. Our other analyses of these data have related melanoma to a number of factors (Beral et al, 1982(Beral et al, , 1983. We therefore stratified the findings for oral contraceptives by a large number of possible confounding factors.…”
Section: Methodsmentioning
confidence: 99%
“…People with fair skin are more likely than those with more pigmented skin to experience erythema, edema, and skin discomfort after solar exposure (28,29), and they are more likely to develop melanoma than those with darker skin (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown strong associations between malignant melanoma and variously defined benign pigmented lesions. These have been defined and assessed in several ways, varying from simply asking the subjects whether or not they thought that they had more than the average number of naevi on their whole body (Beral et al, 1983), having a lay interviewer assess the number of raised naevi on a readily accessible site, the arm (Holman & Armstrong, 1984a) and a careful full body examination with counts of moles by dermatologists (Swerdlow et al, 1984). The increased risks of melanoma in subjects with naevi or moles are high enough to suggest that these lesions could have practical value in identifying high risk subjects.…”
mentioning
confidence: 99%